2022
DOI: 10.1186/s12909-022-03829-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between academic stress, social support, and self-regulatory fatigue among nursing students: a cross-sectional study based on a structural equation modelling approach

Abstract: Background Emphasizes the state of academic stress, social support, and self-regulatory fatigue on the physical and mental development of Chinese nursing students, the purpose of this study was to investigate the relationship between these variables and the mediating role of social support in academic stress and self-regulatory fatigue among a group of undergraduate nursing students in Heilongjiang Province, China, in order to provide a theoretical basis for working to reduce nursing students’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
(46 reference statements)
0
2
0
2
Order By: Relevance
“…The mean score of depressive symptoms among nursing students was 21.23 (SD = 11.23), indicating that 63.5% had a risk for clinical depression using a cutoff score of 16 or greater. The reason might be that undergraduate nursing students are a high-risk group for depression compared with the same-aged general population because of the stressful nature of the nursing profession with its high academic workload ( Alsaqri et al, 2019 , Hwang and Kim, 2022 , Yuhuan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mean score of depressive symptoms among nursing students was 21.23 (SD = 11.23), indicating that 63.5% had a risk for clinical depression using a cutoff score of 16 or greater. The reason might be that undergraduate nursing students are a high-risk group for depression compared with the same-aged general population because of the stressful nature of the nursing profession with its high academic workload ( Alsaqri et al, 2019 , Hwang and Kim, 2022 , Yuhuan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo, os medicamentos foram classificados no nível 1 (grupos anatômicos e terapêuticos) e nível 5 (substância química), conforme o ATC 14 O adoecimento psíquico entre graduandos do curso de Enfermagem é amplamente discutido na literatura científica [16][17][18] . O estresse é apontado como um estado frequente entre estudantes da área da saúde e atribuído à sobrecarga de atividades acadêmicas que desempenham, que incluem prática do cuidado destinado ao outro, atividade com elevada demanda física e emocional 19 .…”
Section: Materiais E Métodosunclassified
“…Studies have shown that populations such as students ( 18 ),nurses ( 19 ), individuals with chronic illnesses ( 20 ) and cancer patients ( 17 ) experience self-regulation fatigue. Factors such as educational level ( 21 ), family economic status ( 22 ), place of residence, and medical insurance ( 23 ) have been proven to significantly influence the level of self-regulation fatigue.…”
Section: Introductionmentioning
confidence: 99%